Verified Software: Theories, Tools, Experiments - Shankar, Natarajan (Springer, 2017)
This volume contains the proceedings of the second working conference on Verified Software: Theories, Tools, and Experiments, VSTTE 2008, held in Toronto, Canada, in October 2008. The 16 papers presented together with 4 invited talks were carefully revised and selected for inclusion in the book. This second conference formally inaugurates the Verified Software Initiative (VSI), a fifteen-year, co-operative, international project directed at the scientific challenges of large-scale software verification. The scope of the cooperative effort includes the sharing and interoperability of tools, the alignment of theory and practice, the identification of challenge problems, the construction of benchmark suites, and the execution of large-scale experiments.